Prevalence of Tongue Lesions in Patients Visiting Private Dental Practices of Pakistan: A Multicenter Study (Medical Forum Monthly, 2022)
Objective: To determine the prevalence of lesions of tongue and their association with gender among dental patients.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Different private dental clinics of Sindh and Punjab province from November 2020 to October, 2021 for a period of one-year.Materials and Methods: The current study comprised of 1500 subjects which were clinically examined in different dental clinics of Sindh and Punjab province (n=768 Male) and n=732 females) Diagnosed patients of tongue lesions, aged between 10 - 90 years of age were selected by using the convenience sampling technique. The existence of various types of lesions was determined by examination of the oral cavity.Results: The frequency of tongue lesion was 14.4%. Coated tongue was found be the most common lesion diagnosed in the present study affecting 89 (41.2%) participants followed by traumatic ulcers 47(21.7%), geographic tongue 38(17.5%) and fissured tongue 17(7.87%). The prevalence was higher among females than males. Among the systemic conditions hypertension was found to be most common followed by diabetes mellitus.Conclusion: Tongue lesions are the major health concern for any dental practitioner. Most of the lesions are easily diagnosed by an experienced clinician except for malignant pathology which requires microscopic examination.